1974
DOI: 10.1042/cs0470415
|View full text |Cite
|
Sign up to set email alerts
|

Unesterified Fatty Acids and the Binding of Tryptophan in Human Plasma

Abstract: 1.The percentage of human plasma tryptophan in the free state (ultrafilterable) was positively and significantly correlated with plasma non-esterified fatty acid (NEFA) concentration.2. Results obtained either by adding tryptophan to plasma in vitro or from plasma taken during tryptophan infusion indicate one tryptophan binding site per albumin molecule and an inverse relationship between binding constants and NEFA concentration.3. A single normal subject was atypical as the apparent number of binding sites va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

1975
1975
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
(12 reference statements)
2
13
1
Order By: Relevance
“…T. Phillipson and E. D. Bird, unpublished work). Central serotoninergic mechanisms are known to be sensitive to alterations in these factors in the rat (Curzon, Friedel, Kantamaneni, Greenwood & Lader, 1974;Fernstrom & Wurtman, 1972; Biggio, Fadda, Fanni, Tagliamonte & Gessa, 1974) and in man (Perez-Cruet, Chase & Murphy, 1974). Therefore serotonin may play a role in the production of the abnormalities in growth hormone secretion described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…T. Phillipson and E. D. Bird, unpublished work). Central serotoninergic mechanisms are known to be sensitive to alterations in these factors in the rat (Curzon, Friedel, Kantamaneni, Greenwood & Lader, 1974;Fernstrom & Wurtman, 1972; Biggio, Fadda, Fanni, Tagliamonte & Gessa, 1974) and in man (Perez-Cruet, Chase & Murphy, 1974). Therefore serotonin may play a role in the production of the abnormalities in growth hormone secretion described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that increasing the amount of plasma tryptophan which is unbound i.e., 'free' also increases brain tryptophan (Knott & Curzon, 1972). Administration of tryptophan produces a rise in both total and free tryptophan concentration but as the binding sitesapproximately one per albumin molecule (Curzon, Friedel, Kantameneni, Greenwood & Lader, 1974)-approach saturation the concentration of free tryptophan rises more rapidly and to a relatively greater extent than does total tryptophan.…”
Section: Introductionmentioning
confidence: 99%
“…As to the decrease of albuminbound serum Trp concentration and the increase of free serum Trp concentration under nephrotic conditions, these changes seem to be due to not only the decrease of serum albumin levels but also the increase of serum NEFA levels. It has been shown in vitro and in vivo that long-chain fatty acids weaken the binding of Trp to albumin (Curzon et al, 1973;Curzon et al, 1974;Brodersen et al, 1989;Sasaki et al, 1993b). In the PAN-treated rats, serum NEFA levels changed in parallel with the changes of albumin-bound serum Trp and free serum Trp levels.…”
Section: Discussionmentioning
confidence: 90%
“…It is known that besides Trp, endogenous substances such as long-chain fatty acids, unconjugated bilirubin, and bile acids bind to albumin (Peter, 1985). In addition, it has been demonstrated in vitro and in vivo that long-chain fatty acids weaken the binding of Trp to albumin (Curzon et al, 1973;Curzon et al, 1974;Brodersen et al, 1989;Sasaki et al, 1993b). Pirazzoli et al (1983) have reported that in children with nephrotic syndrome, a decrease in total plasma Trp levels occurs with an increase in free plasma Trp levels and that there are a positive correlation between albumin and albumin-bound Trp concentrations and a negative correlation between albumin and free Trp concentrations in the plasma.…”
Section: Introductionmentioning
confidence: 99%